Effects of potassium on panicle structure and spikelet morphology of a double grained rice cultivar - Sarwar, AKM Golam; Mridul, Al-Muzahid; Chanda, Sontosh Chandra; Shelley, Israt Jahan (Bangladesh Journal of Botany, 2020)
Influence of K on panicle structure and spikelet morphology of a double grained rice cultivar was evaluated. Results showed that K enhanced the plant height, leaf number, yield and yield contributing descriptors in double grained rice cultivar. The ratio of single-double grained spikelets on a panicle varied from 70 : 30 to 59 : 41. The position of spikelets on a panicle viz. primary vs. secondary branch, middle vs. upper or lower portion of panicle, had little effect on single-double grain ratio. However, K significantly affected the single-double grained spikelet ratio between primary and secondary branches. Multi-grained spikelets showed the potential to increase grain number per panicle thereby increasing rice yield.